Potencial patogênico de cepas ambientais e clínicas de Herbaspirillum spp. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2016)
Nitrogen fixing bacteria are being widely used as biological fertilizers (biofertilizers) as a substitute to chemical compounds. Herbaspirillum genus was first isolated from grasses of agricultural interest in Brazil and, due to their ability to fix atmospheric nitrogen, has been tested as a biofertilizer in some agricultural crops such as sugar cane and corn. However, even being considered a non-pathogenic genus, their interaction mechanism with plants are similar to mechanism of infections from a pathogenic bacterium and recently there have been reports of isolation of these bacteria in hospitalized patients, usually in immunocompromised patients and/or with severe diseases like leukemia and mainly cystic fibrosis. Regarding this, the objective of this study was to evaluate the pathogenic potential of the strains of the genus Herbaspirillum: environmental strain H. seropedicae SmR1 and their modified forms (RAM GFP and ds RED) and the clinical isolated strains H. frisingense AU14559 e H. huttiense AU11883. In vitro tests using reagents MTT and Neutral Red were performed to evaluate lung cells Calu-3 viability following exposure to sterile supernatant of bacterial cultures with 8 and 18 h of growth, showing cytotoxic effect of all different strains of the species H. seropedicae used. Morphology cell tests using the same supernatants induced alterations in Calu-3 cells with all bacterium strains used. Cell adhesion methodology showed that the human isolated strains H. huttiense AU11883 and H. frisingense AU14559 are capable of adhering on Calu-3 cells, being considered low adhesion bacteria. In in vivo assays, using a pneumonia induced model in mice, H. seropedicae SmR1 strain was able to induce severe weight loss in those animals, as well as a rise in total leukocytes count and neutrophils on bronchoalveolar lavage (LBA) and histopathological changes on the lungs, like perivascular and peribronchial infiltrates. The clinical isolated strain from infected lungs, H. huttiense AU11883, showed cytotoxicity and adhesion in vitro, and also histopathological changes on the lungs of intratracheal inoculated animals, but they didn’t show weight loss or significant alterations on LBA. Those results shows that the environmental strain H. seropedicae SmR1 presented evidence confirming its pathogenic potential, but are still required further tests with a larger number of strains to evaluate the pathogenic potential of this bacterial genus.
Keywords: Bactérias fixadoras nitrogênio; Citotoxicidade; Pneumonia; Calu-3; Nitrogen fixing bacteria; Cytotoxicity; Pneumonia; Calu-3; CNPQ::CIENCIAS DA SAUDE::FARMACIA